The Influence of Misinformation on the Health-Related Decision Making of the Samoan People During the Measles Epidemic - Sefo, Caitlin Vaelenoatia Paese (Auckland University of Technology, 2022)
The purpose of this research is to examine the role of misinformation in influencing the health-related decision making of the Samoan people during the 2019 measles epidemic. My interest in this topic emerged when I was in Samoa at the time of the epidemic, I observed a large volume of misinformation being spread online and in person partly stemming from anti-vaccine hesitancy following two babies who died after being administered the MMR vaccine. It was not made known by the government this was due to human error rather than the vaccine itself. This culminated in a health crisis which saw vaccine rates at its lowest point, despite the existence of a safe and effective vaccine. My research investigated the role of misinformation from the perspective of medical professionals. I established the research question: How does the influence of misinformation affect the health-related decision making of the Samoan people during the measles epidemic? Qualitative semi-structured interviews were used an allowed participants to share their individual experiences and offer their own interpretation. I analysed the interviews according to thematic analysis, which allowed me to identify patterns and recurrent themes within the data. These themes were: institutional influence, societal influence and palagi influence. Institutional influence encapsulates participants' thoughts on the role of governing bodies. Most notably the lack of communication and transparency leading up to and throughout outbreak. It was evident from the findings that governing bodies were more concerned with face-saving rather than communicating concise and accurate information to the public. The second theme, societal influence, explores the consultation of traditional medicine and anti-vaccination methods. Findings reveal that many Samoans consulted a traditional healer prior to seeking treatment from the hospital. It became apparent that traditional healers will always be consulted to some degree as it is ingrained in the Samoan culture. Therefore, it is important for the governing bodies to work collaboratively with traditional healers. On the other side of the spectrum, anti-vaccination activists were found to have exploited a vulnerable community for profit by disseminating misinformation. Furthermore, anti-vaxxers were perceived to have more credibility due to their status within society, as they were predominantly white. In conclusion, my research found that governing bodies were not prepared for this health crisis. As a developing nation, the health literacy gap is vast. The lack of communication left an opportunity for anti-vaccination activists to disseminate misinformation and drive real world actions.